Effect of cumulative exposure to psychosocial stressors at work on global cognitive function: A 25‐year longitudinal study: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Duchaine, Caroline S; Brisson, Chantal; Talbot, Denis; Gilbert‐Ouimet, Mahée; Trudel, Xavier; Vézina, Michel; Diorio, Caroline; Giguère, Yves; Milot, Alain; Laurin, Danielle
Abstract: Background: By 2050, an estimated 152 million people will be living with dementia. Prospective studies suggest that exposure to psychosocial stressors at work could be associated with a higher risk of mild cognitive impairment or dementia, but the evidence is still not clear. Method: This study aimed to evaluate the effect of cumulative exposure to psychosocial stressors at work on global cognitive function in a cohort followed for over 25 years. At baseline in 1991‐1993 (T1), 9, 188 white‐collar workers were recruited. Two follow‐ups were carried out in 1999‐2001 (T2) and 2015‐2019 (T3). This analysis was done among 5, 728 participants working in T2, which participated in T3. Global cognitive function was evaluated with the validated Montreal Cognitive Assessment test (Nasreddine, 2005) and categorized in three groups according to standardized cut‐offs. Psychosocial stressors at work were evaluated with the validated Job Content Questionnaire (Karasek, 1979) at each time. The effect of cumulative exposure to psychosocial stressors at work at T1 and T2 on cognitive function categories at T3 was estimated with marginal structural models using inverse probability of treatment and censoring weights. Each observation was weighted for the inverse of the probability of death and lost to follow‐up and adjusted for potential confounders measured at T1 (age, sex, education, number of years in the same job, comorbidities, and lifestyle habits). Multiple imputation of missing data was performed. Result: Workers exposed to low job demand and those exposed to a passive job (low job demand combined with low job control) at both T1 and T2 were at higher risk of moderate to severe cognitive impairment than non‐exposed workers (prevalence ratios (PR) and 95% confidence intervals (CI) of 1.34 (1.10;1.63), p=0.003, and 1.27 (1.05;1.54), p=0.012 respectively). Men, but not women, exposed to low job control at both T1 and T2 were at higher risk of moderate to severe cognitive impairment than non‐exposed workers (PR and 95% CI: 1.38 (1.07;1.79), p=0.015). No statistically significant associations were observed with the risk of mild cognitive impairment. Conclusion: Primary prevention of cognitive impairment could be possible with the reduction of these frequent and modifiable psychosocial stressors at work.